(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
The relationship between the meaning of "pembayang" (or foreshadower) and "maksud" (or meaning) in pantun has been widely mentioned and discussed by scholars but not yet understood as a result of Malay analogical reasoning. These shortcomings are addressed in this article in order to clarify that the reasoning structure of pantun can be explained as a source and tradition of Malay logic in the Malay-Indonesian intellectual history. The existence of pantun logic can be proven by the existence of "well-made" pantun, according to Za`’ba’s classification, and its proposed five scopes, namely: (1) the medium of knowing (i.e. how the units of "pembayang" and "maksud" are composed); (2) the knowing content (i.e. the scope of both units of "pembayang" and "maksud"); (3) the way of analogization (i.e. how "pembayang" can be analogized with "maksud" and the causes of their fallacies); (4) the varieties of analogy (i.e. the types and forms of analogy used in pantun composition), and; (5) the philosophy of logic (i.e. justification of the uniqueness and advantage of pantun logic through analogy). Based on the earliest evidence of pantun from 1371 CE, the written history of pantun logic for over 650 years until today could be rebuilt with the proposed scope of the study above. Keyword: pantun, inference, analogy, logic, Malay